An orchestrator for networked control systems and its application to collision avoidance in multiple mobile robots. (28th May 2021) - Agrawal, Shweta; Jain, Sanjiv Kumar; Ibeke, Ebuka
Networked control system (NCS) consists of controlled distributed nodes while an orchestrator functions as a central coordinator for controlling the distributed tasks. The NCSs have challenges of coordination and right execution sequencing of operations. This paper proposes a framework named controlled orchestrator (COrch) for coordinating and sequencing the tasks of NCSs. An experiment was performed with three robotic vehicles that are considered as individual control system. Furthermore, the proposed orchestrator COrch decided the sequencing of operations of the robots while performing obstacle avoidance task for spatially distributed robots in parallel. COrch is used to control this task by utilising the concept of remote method invocation (RMI) and multithreading. RMI is used to prepare the software for controlling the robots at remote end while multithreading is used to perform parallel and synchronise execution of multiple robots. The remote end software generates signals for sequential, parallel and hybrid mode execution.